The distribution of Angiostrongylus cantonensis (Chen) in the central nervous system of laboratory rats - Limaye, L S; Bhopale, M K; Renapurkar, D M; Sharma, K D (Folia parasitologica, 1983)
The distribution of preadult Angiostrongylus cantonensis helminths in various regions of the central nervous system of rats, infected with varying doses of larvae, was studied. A dose of 10 000 larvae proved to be lethal; the rats showed paralytic symptoms and loss of vision prior to death. A very low dose of 15 larvae also proved to be infective to the central nervous system. Incidence of eye involvement was observed in two rats receiving a dose of 500 larvae. Maximum number of helminths were recovered from the cerebral hemisphere region but their involvement per unit weight of the tissue was found to be highest in the region of medulla oblongata.
Keywords: Angiostrongylus; centrální nervový systém; krysa rodu Rattus; Nematode Infections; Male; Larva; larva; Animals; Central Nervous System; Female; mužské pohlaví; ženské pohlaví; nematodózy; zvířata; Rats